Spatial distribution, ecological and health risk assessment of heavy metals in marine surface sediments and coastal seawaters of fringing coral reefs of the Persian Gulf, Iran. (October 2017) - Ranjbar Jafarabadi, Ali; Riyahi Bakhtiyari, Alireza; Shadmehri Toosi, Amirhossein; Jadot, Catherine
Abstract: Concentrations of 13 heavy metals (Al, Fe, Mn, Zn, Cu, Cr, Co, Ni, V, As, Cd, Hg, Pb) in 360 reef surface sediments (0–5 cm) and coastal seawater samples from ten coral Islands in the Persian Gulf were analyzed to determine their spatial distribution and potential ecological risks. Different sediment quality indices were applied to assess the surface sediment quality. The mean concentrations of metals in studied sediments followed the order: Al > Fe > Ni > V > Mn > Zn > Cu > Cr > Co > As > Cd > Pb > As. Average Cd and Hg exceeded coastal background levels at most sampling sites. With the exception of As, concentrations of heavy metals decreased progressively from the west to the east of the Persian Gulf. Based on the Enrichment Factor (EF) and Potential Ecological Risk Index (RI), concentrations of V, Ni, Hg and Cd indicated moderate contamination and is of some concern. The mean values of heavy metals Toxic Units (TUs) were calculated in the following order: Hg (0.75)> Cr (0.41)> Cd (0.27)> As (0.23)> Cu (0.12)> Zn (0.05)> Pb (0.009). Furthermore, the mean contributing ratios of six heavy metals to Toxic Risk Index (TRI) values were 79% for Hg, 11.48% for Cd, 6.16% for Cr, 3.27% for Cu, 0.07% for Zn and 0.01% for Pb. Calculated values of potential ecological risk factor, revealed that the risk of the heavy metals followed the order Cd > Pb > Ni > Cr > V > Cu > Zn. The results reflected that the level of heavy metals, especially Hg and Cd, are on rise due to emerging oil exploration, industrial development, and oil refineries along the entire Gulf. Fe, Mn, Cu, Zn, V and Ni concentrations in seawater were significantly higher (p < 0.05) than the other detected dissolved heavy metals in the sampling sites. A health risk assessment using the hazard quotient index (HQ) recommended by the USEPA suggests that there is no adverse health effect through dermal exposure, and there is no carcinogenic and non-carcinogenic harm to human health. Graphical abstract: Highlights: East part of the Persian Gulf is less contaminated as compared to the west part. The main source of the HMs in the Persian Gulf is oil/industrial activities. Compared to another indices, the CSI and TRI indicated much more sensitivity. Non-cancer and cancer risks posed by all the 13 dissolved HMs are minimal.